DIGITAL MARKETIG DALAM PEMBERDAYAAN MASYARAKAT BERBASIS POTENSI LOKAL (KARAWO) DI DESA BONGOHULAWA KABUPATEN GORONTALO - Ismail, Nurwita; Talawanu, Andre; Rauf, Irma; Ali, Fajar; Batalipu, Irawati; Aminullah, Natasya; Dude, Nurjanna; Bakar, Dian; Santoso, Triyadi (Universitas Gorontalo, 2025)
Based on one of the core programs selected from this Community Service activity, namely Karawo craftsmen. After observation, there are problems and lack of empowerment in MSMEs causing these MSMEs to not develop well. In general, the problems faced by Karawo MSMEs are only used for service fees which are very minimal for working on a Karawo. The method of implementing this work program is carried out in 6 stages, namely the observation stage, the activity program determination stage, the budget determination stage, the activity implementation time determination stage, the activity implementation stage, and the last is the final activity report preparation stage. The results of the implementation of this program received good support from the government and the Bongohulawa village community carried out by students of the Community Service Program (KKP). In this case, students created Digital Marketing Socialization and Training with the aim of creating Digital Marketing strategies for local businesses so that the community can also manage their own businesses.